The role of IL-10 in Infected Mice Due to Visceral Leishmaniasis : Peran IL-10 pada Tikus yang Terinfeksi Karena Leishmaniasis Visceral - Abdulsada , Amal kamil (Universitas Muhammadiyah Sidoarjo, 2024)
act. In this study, 30 Balb mice were inoculated with Leishmania donovani amastigote which was taken from a farm for growing visceral leishmaniasis, and 20 healthy Balb mice were taken as a control group. The mice ages ranged between (4-11) months. The study was conducted at the Veterinary Research Center in Diyala province during the period from March 2024 to January 2025. The results showed that the mean age of mice infected with visceral Leishmaniasis was (4-7) months 11 (22.0%) compared to the controls 8 (16.0%), and the mean age (8-11) was 18 (36.0%) compared to the controls 31 (62.0%) with no significant differences (P= 0.99). The prevalence of Leishmania donovani infection in male mice was 20 (40.0%) compared to the controls 36 (72.0%), which was more than females 9 (18.0%) compared to the controls with no significant variations (p=0.57). The mean level of anti Leishmania donovani IgG mice antibodies was (2.49±2.67) compared to the controls (0.83±0.57) with a highly significant variation (P= 0.003), and the mean level of IL-10 was (22.09±8.12) with a highly significant difference (P≤0.0001). The mean level of anti-leishmania donovani mice IgG antibodies in males was (2.74±3.18) compared to the controls (0.75±0.26) and the mean level of anti-leishmania donovani mice IgG antibodies in females was (20.55±0.67) compared to the controls (1.10±1.13) with no significant differences (P=0.52). While the mean level of IL-10 in males was (22.79±8.97) compared to the controls (4.81±1.91) and mean level of IL-10 in females was (20.55±6.00) compared to the controls (10.12±11.57) with no significant differences (P=0.36). The mean level of anti-leishmania donovani antibodies in mice age (4-7) months was (1.99±0.83) compared to the controls (0.68±0.26) and the mean level of anti-leishmania donovani antibodies in mice age (8-11) months was (2.79±3.33) compared to the controls (0.70±0.19) with no significant differences (P=0.26). While the mean level of IL-10 in age (4-7) months was (21.97±8.30) compared to the controls (1.70±0.60) and mean level of IL-10 in age (8-11) months was (22.16±8.25) compared to the controls (7.33±2.03) with no significant differences (P=0.24). There were a direct correlations between Leishmania donovani mice IgG antibody levels and IL-10 levels with (r=. 337*,. 337*) respectively. The correlations were highly significant (P=0.05), while our findings also showed negative correlations between Leishmania donovani mice IgG antibody level and ages at (r=-.-.001) and sex at (r=-.042) with (P= .994) and (P=.775) respectively. A mutation happened in IL-10 genes at rs1800876 SNPs, and wild TT was altered to CC & TC respectively in comparison to the control group with visceral leishmanial mice infection. Highlights: No age or sex impact – Infection prevalence showed no significant differences. Strong immune response – Higher IgG and IL-10 levels in infected mice. Genetic mutation detected – IL-10 gene mutation linked to infection. Keywords: IL-10, mice, visceral Leishmaniasis